Representation of Gender Inequality in Eka Kurniawan’s Cantik Itu Luka: A Feminist Review - Tanjung, Tia Wulandari; Hayati, Yenni (Universitas Cokroaminoto Palopo, 2025)
This study examines the representation of gender injustice in Eka Kurniawan’s novel Cantik Itu Luka through a qualitative content analysis approach. The research focuses on five dominant forms of gender-based oppression: stereotyping, violence, double burden, marginalization, and subordination. These categories were applied to classify and interpret the narrative elements such as character, plot, and thematic structure that reflect unequal gender relations within the text. Data were collected through a thorough textual reading, supported by keyword identification and classification based on feminist theory, particularly radical and postcolonial feminism. The results reveal that stereotyping is the most frequently occurring form of injustice, where female characters are often labeled as immoral, dishonorable, or inherently inferior. Acts of violence against women, both physical and symbolic, are portrayed as normalized responses within patriarchal and militaristic structures. The novel also depicts how female characters experience a double burden working in both domestic and economic spheres without recognition or compensation. Furthermore, women's access to education, agency, and public space is repeatedly denied, reinforcing their marginalization. While subordination appears less frequently, it is ideologically significant in shaping the female characters’ roles as submissive, obedient, and sacrificial figures. Despite focusing on a single literary work, this study contributes to the development of feminist literary criticism in Indonesia by demonstrating how narrative fiction can reflect, reinforce, and challenge prevailing gender ideologies. The study also offers insights for further interdisciplinary research and critical literacy practices centered on gender equity.